Legal and Ethical Implications of the Over Criminalization of Illegal Immigrants in the United States (Tema Central) - Gallegos, María del Mar (2017)
The aim of this review is to explore the consequences of the incorporation of criminal law into immigration enforcement. It will argue that the measures accompanying this criminalization of migration undermine human rights and legal principles. This essay first provides a brief view of the contemporary patterns of migration. Second, it analyses the shift that has occurred in international migration law from the civil to the criminal realm, drawing on the illustrative example of Latin American immigration into the United States. Finally, it suggests some challenges that both domestic and international law are facing and the importance of these from a criminological point of view.